Expertise‐based randomized clinical trial of laparoscopic versus small‐incision open cholecystectomy (Br J Surg 2013; 100: 886–894). Issue 3 (February 2014) - Naraynsingh, V.; Singh, Y.; Dan, D.; Maharaj, R.
<x xml:space="preserve">Abstract</x> The Editors welcome topical correspondence from readers relating to articles published in the Journal. Responses should be sent electronically via the BJS website (www.bjs.co.uk). All letters will be reviewed and, if approved, appear on the website. A selection of these will be edited and published in the Journal. Letters must be no more than 250 words in length.